Manajemen Kecerdasan Emosi dan Penerapan Administrasi Skrining Penyakit Tidak Menular bagi Kader Posyandu - Tri Wulandari Wulandari Kesetyaningsih; Tri Pitara Mahanggoro (Smart Society Empowerment Journal, 2022)
Background : Gamping Kidul hamlet is growing fast as an educational center. This condition brings socio-economic changes and unhealthy lifestyles so that there are concerns about an increase in non-communicable diseases (NCDs). This Community Service (CS) is a continuation of the previous CS which has formed a care group of healthy lifestyles and provides cadres with NCDs screening and prevention. These activities were enhanced by training on emotional intelligence management and screening administration. The activity aims to train management emotions and apply NCDs screening administration so that it can further strengthen the ability of cadres to implement NCDs prevention programs. Methods :The service is carried out with explanation, discussion, and practice. At the end of the training, an assessment of the level of emotional intelligence is carried out. Results : The training was attended by 14 integrated service post cadres (posyandu) as participants. The results of the assessment show that 57% of cadres have high emotional intelligence, 29% are moderate and 14% are low. Emotional intelligence of non-cadres is 84.62% high and 7.69% moderate and low, respectively. The Mann Whitney test proves that the emotional intelligence of cadres is significantly lower than that of non-cadres. Conclusion : It was concluded that most posyandu cadres had high emotional intelligence, some were moderate-low, but lower than non-cadres in average. Posyandu has never done NCDs screening. The training has provided experience in NCDs screening for posyandu cadres.